If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -80000x + 25 + -4999 = 8000x + -593 + 3434 + -697865 + 86765 Reorder the terms: 25 + -4999 + 3x + -80000x = 8000x + -593 + 3434 + -697865 + 86765 Combine like terms: 25 + -4999 = -4974 -4974 + 3x + -80000x = 8000x + -593 + 3434 + -697865 + 86765 Combine like terms: 3x + -80000x = -79997x -4974 + -79997x = 8000x + -593 + 3434 + -697865 + 86765 Reorder the terms: -4974 + -79997x = -593 + 3434 + -697865 + 86765 + 8000x Combine like terms: -593 + 3434 = 2841 -4974 + -79997x = 2841 + -697865 + 86765 + 8000x Combine like terms: 2841 + -697865 = -695024 -4974 + -79997x = -695024 + 86765 + 8000x Combine like terms: -695024 + 86765 = -608259 -4974 + -79997x = -608259 + 8000x Solving -4974 + -79997x = -608259 + 8000x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8000x' to each side of the equation. -4974 + -79997x + -8000x = -608259 + 8000x + -8000x Combine like terms: -79997x + -8000x = -87997x -4974 + -87997x = -608259 + 8000x + -8000x Combine like terms: 8000x + -8000x = 0 -4974 + -87997x = -608259 + 0 -4974 + -87997x = -608259 Add '4974' to each side of the equation. -4974 + 4974 + -87997x = -608259 + 4974 Combine like terms: -4974 + 4974 = 0 0 + -87997x = -608259 + 4974 -87997x = -608259 + 4974 Combine like terms: -608259 + 4974 = -603285 -87997x = -603285 Divide each side by '-87997'. x = 6.855745082 Simplifying x = 6.855745082
| 3p+q+4p= | | 3x-80000x+25-4999=8000x-593+3434 | | 3r-5=10-7r | | -13+6y+13p-2y-4p+17= | | 7/12=84/x | | 120=x+130+2 | | 1.19+.39=3.92 | | logx^16=-2 | | 3x^2-12=60 | | x^2-y^2+z^2-4x+2y+2z+2=0 | | x+.05x=1 | | 3a+a-15=225 | | 5x^2+0x+10=0 | | (v-1/2)(v-1/5) | | 3a+b=a-15 | | 3a-7a=7 | | b=3a+b | | 9h=27 | | 1/2(t-6)-4/3(t-2)-3/4t-2 | | 3a+a=225 | | 4(3a-1)+2(a+3)=20 | | 11{(20-11m)/4} | | 2/3z=4:1/4 | | 6/4=27/x | | 4(3a+1)+2(a-3)=20 | | 10x^2+150x+500=0 | | 4x+44+6x+36=x | | x^2-4x+7=12 | | 5-(6y+9)+2y=2(2+1) | | 0.25(x)=8(x+4) | | 2+2(x-1)=6 | | y^2+9-6y= |